Logic-Based Program Synthesis and Transformation : 25th International Symposium, LOPSTR 2015, Siena, Italy, July 13-15, 2015. Revised Selected Papers - Falaschi, Moreno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 25th International Symposium on Logic-Based Program Synthesis and Transformation, LOPSTR 2015, held in Siena, Italy, in July 2015. The 21 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 30 submissions. The aim of the LOPSTR series is to stimulate and promote international research and collaboration on logic-based program development. LOPSTR is open to contributions in all aspects of logic-based program development, all stages of the software life cycle, and issues of both programming-in-the-small and programming-in-the-large.
Semantics of Logic Languages -- Ecient compilation of functional logic programs -- Types and security -- Optimization -- Static analysis -- Automated Verication -- Program debugging and slicing -- Smart Environments -- Program Transformation -- Constraint Solving and Programming. .
Keywords: Logic design; Software engineering; Computer science; Artificial intelligence; Computational complexity; Logics and Meanings of Programs; Software Engineering/Programming and Operating Systems; Mathematical Logic and Formal Languages; Artificial Intelligence; Discrete Mathematics in Computer Science